Effect of Credit Management on Liquidity Position of Selected Manufacturing Firms in Nigeria - Onyeike, Bright Chigemecha (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Credit serves as the life blood of modern commerce, as its efficient management is crucial for business survival. Overtime the issues of credit risk has continued to pose significant challenge to businesses, necessitating an innovative research and possible solutions. This study examined effect of credit management on liquidity position of manufacturing firms in Nigeria. The specific objectives of this study are to: determine the effect of account receivable period, account payable period, and cash conversion cycle on current ratio of listed manufacturing firms in Nigeria, using a panel regression model to ascertain the impacts at a 5% level of significance. Ex post facto research design was adopted, and data were sourced from the annual reports of twelve (12) manufacturing firms in the consumer and industrial goods sector listed in the Nigerian exchange group (NGX) for a period of ten years (2014-2023). Data were analyzed using the fixed effect panel regression model. Research findings shows that account receivable period and account payable period have a negative effect on current ratio, while cash conversion cycle was seen to have a positive effect on current ratio. This study recommends that manufacturing firms should strike a balance between maintaining effective credit management practices, effective internal control mechanisms and good customer relations. It is advisable that firms should negotiate favorable terms that allow for flexibility without straining cash reserves, thus safeguarding liquidity, however, firms should ensuring that resources are not unnecessarily tied up in working capital to avoid risk of high leverage.